2021
DOI: 10.1016/j.atmosenv.2021.118276
|View full text |Cite
|
Sign up to set email alerts
|

Study on the variation of air pollutant concentration and its formation mechanism during the COVID-19 period in Wuhan

Abstract: To prevent the spread of COVID-19 (2019 novel coronavirus), from January 23 to April 8 in 2020, the highest Class 1 Response was ordered in Wuhan, requiring all residents to stay at home unless absolutely necessary. This action was implemented to cut down all unnecessary human activities, including industry, agriculture and transportation. Reducing these activities to a very low level during these hard times meant that some unprecedented naturally occurring measures of controlling emissions were executed. Iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Among all the national controlled air pollutants, NO 2 decreased the most during the COVID-19 lockdown to 52% in a statistically significant way. Travel restrictions during the lockdown caused the most significant reduction in NO 2 , consistent with previous studies [39,40,[61][62][63].…”
Section: Aqi and Online Six National Controlled Air Pollutantssupporting
confidence: 91%
“…Among all the national controlled air pollutants, NO 2 decreased the most during the COVID-19 lockdown to 52% in a statistically significant way. Travel restrictions during the lockdown caused the most significant reduction in NO 2 , consistent with previous studies [39,40,[61][62][63].…”
Section: Aqi and Online Six National Controlled Air Pollutantssupporting
confidence: 91%
“…A wide array of meteorological factors including particulate matter, air pollution, and heat were identified as positively associated with the spread of COVID-19. Studies identified that reported on the relationship between meteorological parameters and COVID-19 spread in different regions of the world [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ] are shown in Table 1 . The interplay among meteorological factors (air pollution, meteorological parameters, and climate change) ...…”
Section: Resultsmentioning
confidence: 99%
“…The Community Multiscale Air Quality modeling system of USEPA was used to simulate the spatial and temporal variation of air pollutants during lockdown period. PM 2.5 concentration showed a significant decrease during lockdown, while O 3 levels were found to increase which was attributed to wind direction [ 46 ] Fourteen (14) provinces in China PM 2.5 , PM 10 , SO 2 , NO 2 , and O 3 concentrations and COVID-19 cases Pollutant data were obtained from the China Air Quality Online Monitoring and Analysis Platform. The number of COVID cases, discharges, and deaths during the epidemic period were obtained from the Urban Health Commission.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, all provinces in China successively implemented a national emergency to respond to major public health emergencies. The pollutant emissions decreased because human activities reduced during the lockdown (Filonchyk et al, 2020;Forster et al, 2020;Ghahremanloo et al, 2021;Keller et al, 2021;Li et al, 2020Li et al, , 2021Miyazaki et al, 2020;Huang et al, 2021a;Zhan and Xie, 2022;. For example, Huang et al (2021b) estimated NO x emissions over China during this period, and found a decreased trend owing to human activity reduction.…”
Section: Introductionmentioning
confidence: 99%